Kontribusi Usahatani Kakao terhadap Pendapatan Rumah Tangga Petani di Desa Pangsan, Kecamatan Petang, Kabupaten Badung - ELTA DINA PARTIWI; I WAYAN BUDIASA; I WAYAN WIDYANTARA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Contribution of Cocoa Farming to Farmers Household Incomein Pangsan Village, Petang District, Badung Regency The study aims to determine the sources of cocoa farmers' income, and the largecontribution of cocoa farming to the income of the farmers' households in PangsanVillage, as well as to find out the physical management practices and postharvesthandling applied by the cocoa farmers. The technique of determining the sample wasby using proportional random sampling and the sample was taken randomly to selectthe sample by lottery method with the number of samples of 34 cocoa farmers. Thedata collection was conducted from early February to the end of February 2017. Thestudy used farming analysis to calculate net income and total household income ofcocoa farmers during 2016. The results showed that cocoa farming has the highestcontribution of 70.10% of the total household income of farmers amounting to Rp.85,954,990.80 / year with an average income of Rp. 60,252,258 / year. The physicalmanagement practices of cocoa farming applied by cocoa farmers in Pangsan Villageare in accordance with the physical management practices in the cocoa GoodAgricultural Practices (GAP) guidelines, and it is known that farmers did not applyGood Handling Practices (GHP) to postharvest handling.